Low-frequency polarized electric field promotes stilbene biosynthesis by redirecting phenylpropanoid flux in postharvest grapes - Jie Zhu; Huangqiao Tao; Shi Chen; Linyu Nian; Mengjun Wang; Fei Li; Xu Lu; Chongjiang Cao (Food Chemistry, 2026)

Inhibition of miR ‐33 Alleviates Inflammation Response in Ctenopharyngodon idella Kidney Cells Induced by Chloroquine/Lipopolysaccharide - Lulu Yang; Mengjun Lin; Weifang Zhao; Yuru Zhang; Xinxin Xu; Xianglin Cao; Ronghua Lu (Journal of Fish Diseases, 2026)
A previous study in our laboratory revealed that microRNA‐33 (miR‐33) regulated autophagy initiation and inflammatory response by targeting Atg5 ; furthermore, in this study, chloroquine (CQ), lipopolysaccharide (LPS) and the miR‐33 inhibitor were transfected into Ctenopharyngodon idella kidney (CIK) cells to explore whether miR‐33 regulated late‐stage autophagy and inflammatory response induced by LPS. The results showed that CQ inhibited the fusion of autophagosome and lysosome and significantly increased the secretion of pro‐inflammatory cytokines ( p p beclin‐1 , atg5 , atg7 and atg12 did not recover after inhibiting miR‐33 ( p > 0.05). But the expression of tnf‐α , il‐6 , il‐1β , il‐8 and nf‐κb , as well as the secretion of TNF‐α, IL‐6, IL‐12 and IL‐1β, were significantly downregulated, and the activities of ALP, SOD and CAT were significantly increased ( p p tnf‐α , il‐6 , il‐1β , il‐8 and nf‐κb ; inhibiting the secretion of TNF‐α, IL‐6, IL‐12 and IL‐1β; and increasing the activities of ACP, ALP, SOD and CAT ( p

Sodium alginate/carboxymethyl chitosan/gelatin-naringenin pH-responsive hydrogel beads for oral delivery of traditional Chinese herbal medicines - Zixing Yan; Qingling Nie; Jiajia Liu; Jingxin Chen; Youmei Liu; Yudong Lu; Mengjun Xu; Zhenwen Lin (Carbohydrate Polymers, 2025)

MiR ‐33‐Mediated Regulation of Autophagy and Inflammation in CIK Cells Through Atg5 - Lulu Yang; Mengjun Lin; Weifang Zhao; Yuru Zhang; Xinxin Xu; Xianglin Cao; Guoxing Nie; Ronghua Lu (Journal of Fish Diseases, 2025)
MicroRNA‐33 (miR‐33) plays a critical role in the regulation of autophagy and inflammatory responses. In this study, C. idella kidney (CIK) cells were transfected with a miR‐33 mimic or inhibitor and Atg5 was overexpressed or silenced to elucidate the regulatory mechanism of miR‐33. Our findings revealed that the miR‐33 mimic significantly decreased the expression of LC3B (a marker of autophagy activation), and the level of autophagy‐related genes ( Beclin‐1 , Atg5 and LC3‐1 ) was also significantly downregulated ( p p Beclin‐1 and Atg5 ( p p Atg5 as a direct target gene of miR‐33. Overexpression of Atg5 significantly upregulated the levels of Beclin‐1 , Atg5 , Atg4C and LC3‐1 , along with a reduction in the secretion of proinflammatory factors (TNF‐α, IL‐12 and IL‐1β). Besides, the activities of superoxide dismutase (SOD) and catalase (CAT) were significantly increased ( p Atg5 expression caused significant downregulation in the expression levels of Beclin‐1 , Atg5 , Atg12 , Atg4C and LC3‐1 , resulting in increased secretion of TNF‐α, IL‐12 and IL‐1β and decreased activity of acid phosphatase (ACP) and SOD ( p Atg5 . This study not only enhances the understanding of the mechanism by which miR‐33 regulates autophagy and inflammation in fish but also provides a theoretical foundation and novel insights to improve disease management in the fish aquaculture industry.

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

The effect of environmental regulation on the high-quality development of the iron and steel industry—the case of China - Lingling Guo; Mengjun Lu; Ying Qu (Clean Technologies and Environmental Policy, 2024)

A novel fluorescence immunoassay for the quantitative detection of florfenicol in animal-derived foods based on ZnCdSe/ZnS quantum dot labelled antibody - Cheng Xin; Jingming Zhou; Yumei Chen; Yankai Liu; Hongliang Liu; Chao Liang; Xifang Zhu; Ying Zhang; Zhuting Chen; Xueyuan Tang; Bingxue Zhang; Mengjun Lu; et al. (Food Chemistry, 2024)

A novel coupled algorithm for Studying the performance characteristics of water ramjet in the flight of supercavitating vehicle - Yanxi Yang; Mengjun Wang; Junpeng Liu; Pingan Liu; Lu Wang (Ocean Engineering, 2024)

Analysis of binding and authentic virus-neutralizing activities of immune sera induced by various monkeypox virus antigens - Shuo Song; Zuning Ren; Jiayin Chen; Mengjun Li; Yushan Jiang; Yingxia Liu; Bao Zhang; Hongzhou Lu; Wei Zhao; Chenguang Shen; Yang Yang (Immunologic Research, 2024)

Coordinated responses of rice (Oryza sativa) to the stresses of benzotriazole ultraviolet stabilizers (BZT-UVs): Antioxidative system, photosynthetic activity, and metabolic regulation - Huijun Liu; Mengjun Wang; Siyuan Jin; Qian Guo; Shuping Wang; Haohua Ni; Hainan Lu; Zhiheng Li (Journal of Hazardous Materials, 2024)

Multi-Scale Higher-Order Dependencies (MSHOD): Higher-Order Interactions Mining and Key Nodes Identification for Global Liner Shipping Network - Yude Fu; Xiang Li; Jichao Li; Mengjun Yu; Xiongyi Lu; Qizi Huangpeng; Xiaojun Duan (Journal of Marine Science and Engineering, 2024)
Liner shipping accounts for over 80% of the global transportation volume, making substantial contributions to world trade and economic development. To advance global economic integration further, it is essential to link the flows of global liner shipping routes with the complex system of international trade, thereby supporting liner shipping as an effective framework for analyzing international trade and geopolitical trends. Traditional methods based on first-order global liner shipping networks, operating at a single scale, lack sufficient descriptive power for multi-variable sequential interactions and data representation accuracy among nodes. This paper proposes an effective methodology termed “Multi-Scale Higher-Order Dependencies (MSHOD)” that adeptly reveals the complexity of higher-order interactions among multi-scale nodes within the global liner shipping network. The key step of this method is to construct high-order dependency networks through multi-scale attributes. Based on the critical role of high-order interactions, a method for key node identification has been proposed. Experiments demonstrate that, compared to other methods, MSHOD can more effectively identify multi-scale nodes with regional dependencies. These nodes and their generated higher-order interactions could have transformative impacts on the network’s flow and stability. Therefore, by integrating multi-scale analysis methods to mine high-order interactions and identify key nodes with regional dependencies, this approach provides robust insights for assessing policy implementation effects, preventing unforeseen incidents, and revealing regional dual-circulation economic models, thereby contributing to strategies for global, stable development.

Experimental investigation of high-temperature water vapour ventilated supercavitation - Yanxi Yang; Lu Wang; Hao Chang; Pingan Liu; Mengjun Wang (Ocean Engineering, 2024)

Global recovery patterns of soil microbes after fire - Mengjun Hu; Jiali Wang; Longlong Lu; Haoran Gui; Shiqiang Wan (Soil Biology and Biochemistry, 2023)

Effects of decreased precipitation and thinning on soil respiration in a temperate forest: A one-year field experiment in Central China - Jiali Wang; Hao Liu; Mengjun Hu; Yue Du; Yanchun Liu; Longlong Lu; Shijie Han (CATENA, 2023)

Fatty hepatocyte-derived exosomal miR-122 promotes lipid synthesis and reduces immunocompetence in grass carp (Ctenopharyngodon idella) - Ronghua Lu; Lulu Yang; Wenya Zhang; Shenzong Jia; Mengjun Lin; Jian Sun; Yuru Zhang; Guoxing Nie (Aquaculture, 2023)

Future hot topics and directions of green growth based on a hybrid method - Lingling Guo; Mengjun Lu; Miao Cui; Jingtong Luo (Environmental Science and Pollution Research, 2022)

The effect of salt on the evolution of a subsalt sandstone reservoir in the Kuqa foreland basin, western China - Hai Wu; Mengjun Zhao; Qingong Zhuo; Xuesong Lu; Long Wang; Weiqiang Li; Ya Deng (Carbonates and Evaporites, 2020)